THE DEATH PENALTY IN LEGAL LITERATURE: A Study of Indonesian Law and International Human Rights - Fauzan Fauzan (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2021)
The use of the death penalty in criminal law to achieve the aims of criminal law has sparked much controversy among criminal law professionals. The advantages and disadvantages of adopting death punishment to meet the aims of criminal law, such as providing a sense of security, justice, and so on. In the hierarchy of rules and regulations in Indonesia, the 1945 Constitution is the highest source of legislation. Article 28 (a) of the Indonesian constitution guarantees the right to life and provides that everyone has the right to survive and defend his or her life and existence. As a result, the right to life is a constitutional guarantee. Thus the right to life is a constitutional right. The United Nations also issued a guide entitled Safeguards Guaranteeing Protection of the Rights of Those Facing the Death Penalty through UN Economic and Social Council Resolution 1984/50, dated 25 May 1984. This guide clarifies discussions on the practice of the death penalty under the International Covenant on Civil and Political Rights. Mempersoalkan hukuman mati dalam hukum pidana sebagai sarana mencapai tujuan dari hukum pidana itu sendiri telah banyak menimbulkan perdebatan antar sesama ahli hukum pidana. Pro dan kontra terhadap penggunaan sarana pidana mati sebagai sarana untuk mencapai tujuan hukum pidana, yaitu memberikan rasa aman memberikan keadilan dan sebagainya. Undang-Undang Dasar 1945 adalah sumber hukum tertinggi dalam tata urutan Peraturan Perundang-undangan di Indonesia. Konstitusi Indonesia mengatur ketentuan tentang hak hidup, pasal 28 (a) konstitusi Indonesia melindungi hak hidup dan menyatakan bahwa setiap orang berhak untuk hidup serta mempertahankan hidup dan kehidupannya. Dengan demikian hak hidup merupakan hak konstitusional. PBB juga mengeluarkan sebuah panduan berjudul jaminan perlindungan bagi mereka yang menghadapi hukuman mati ( Safeguards Guaranteeing Protection of the Rights of Those Facing the Death Penalty) melalui Resolusi Dewan Ekonomi Sosial PBB 1984/50,tertanggal 25 Mei 1984. Panduan ini memperjelas pembahasan praktik hukuman mati menurut Kovenan Internasional Hak-Hak Sipil dan Politik